2001
DOI: 10.1046/j.1365-313x.2001.00939.x
|View full text |Cite
|
Sign up to set email alerts
|

The MuDR transposon terminal inverted repeat contains a complex plant promoter directing distinct somatic and germinal programs

Abstract: The Mu transposons of maize are under stringent developmental control. Elements excise at high frequencies in terminally dividing somatic cells, but not in meristems. Mu elements in germinal cells amplify, without excision, and insert throughout the genome. All activities require MuDR, which encodes two genes, mudrA and mudrB, whose near-identical promoters are located in the transposon terminal inverted repeats (TIR). We have fused the 216 bp TIR of the mudrB gene to GUS and luciferase reporters. We demonstra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(32 citation statements)
references
References 49 publications
2
30
0
Order By: Relevance
“…Evolutionary analysis of these genes has confirmed that the FHY3/FAR1 gene family has been co-opted from one or several related Mutator elements [41]. The maize Mutator transposase MURA is known to regulate the expression of both its own genes and occasionally adjacent genes [43][44][45]. Thus, it appears that FHY3 and FAR1 have retained the transcriptional activity of an ancestral Mutator transposase.…”
Section: Plantsmentioning
confidence: 92%
“…Evolutionary analysis of these genes has confirmed that the FHY3/FAR1 gene family has been co-opted from one or several related Mutator elements [41]. The maize Mutator transposase MURA is known to regulate the expression of both its own genes and occasionally adjacent genes [43][44][45]. Thus, it appears that FHY3 and FAR1 have retained the transcriptional activity of an ancestral Mutator transposase.…”
Section: Plantsmentioning
confidence: 92%
“…The widespread transposon activation proposed in McClintock's genome shock theory could also result in alterations to gene expression, either by knocking out gene activity or creating novel promoter function. Indeed, it has been shown that transposable elements can sometimes drive transcription if inserted upstream of a coding region (Barkan & Martiennssen 1991;Raizada et al 2001).…”
Section: Changes To Gene Expression In Hybridsmentioning
confidence: 99%
“…The region at ±95 to ±124 (indicated in dark gray) has strong homology to histone hexamer and nonamer motifs as well as the B cyclin (MSA) enhancer. The region at position ±22 to ±76 (hatched box) shows high nucleotide sequence identity to the pollen enhancers of the tomato genes LAT59 and LAT52, and the maize gene ZM13 (M. Raizada et al 2001). B Plasmids used in this study.…”
Section: Introductionmentioning
confidence: 99%